If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 8)(2x + -4) = 1008 Reorder the terms: (8 + X)(2x + -4) = 1008 Reorder the terms: (8 + X)(-4 + 2x) = 1008 Multiply (8 + X) * (-4 + 2x) (8(-4 + 2x) + X(-4 + 2x)) = 1008 ((-4 * 8 + 2x * 8) + X(-4 + 2x)) = 1008 ((-32 + 16x) + X(-4 + 2x)) = 1008 (-32 + 16x + (-4 * X + 2x * X)) = 1008 (-32 + 16x + (-4X + 2xX)) = 1008 Reorder the terms: (-32 + -4X + 16x + 2xX) = 1008 (-32 + -4X + 16x + 2xX) = 1008 Solving -32 + -4X + 16x + 2xX = 1008 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '32' to each side of the equation. -32 + -4X + 16x + 32 + 2xX = 1008 + 32 Reorder the terms: -32 + 32 + -4X + 16x + 2xX = 1008 + 32 Combine like terms: -32 + 32 = 0 0 + -4X + 16x + 2xX = 1008 + 32 -4X + 16x + 2xX = 1008 + 32 Combine like terms: 1008 + 32 = 1040 -4X + 16x + 2xX = 1040 Add '-16x' to each side of the equation. -4X + 16x + -16x + 2xX = 1040 + -16x Combine like terms: 16x + -16x = 0 -4X + 0 + 2xX = 1040 + -16x -4X + 2xX = 1040 + -16x Reorder the terms: -1040 + -4X + 16x + 2xX = 1040 + -16x + -1040 + 16x Reorder the terms: -1040 + -4X + 16x + 2xX = 1040 + -1040 + -16x + 16x Combine like terms: 1040 + -1040 = 0 -1040 + -4X + 16x + 2xX = 0 + -16x + 16x -1040 + -4X + 16x + 2xX = -16x + 16x Combine like terms: -16x + 16x = 0 -1040 + -4X + 16x + 2xX = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-520 + -2X + 8x + xX) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-520 + -2X + 8x + xX)' equal to zero and attempt to solve: Simplifying -520 + -2X + 8x + xX = 0 Solving -520 + -2X + 8x + xX = 0 Move all terms containing X to the left, all other terms to the right. Add '520' to each side of the equation. -520 + -2X + 8x + 520 + xX = 0 + 520 Reorder the terms: -520 + 520 + -2X + 8x + xX = 0 + 520 Combine like terms: -520 + 520 = 0 0 + -2X + 8x + xX = 0 + 520 -2X + 8x + xX = 0 + 520 Combine like terms: 0 + 520 = 520 -2X + 8x + xX = 520 Add '-8x' to each side of the equation. -2X + 8x + -8x + xX = 520 + -8x Combine like terms: 8x + -8x = 0 -2X + 0 + xX = 520 + -8x -2X + xX = 520 + -8x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| -5(3y-9)-y=-3(y-5) | | 3x+7=-12 | | -7=z/8-2 | | 3*3x=2*5x+5*6 | | 3*3x=2.5x+5*6 | | 7-41x=2 | | z-(v+u)=-10 | | b=-8-(v-y) | | 8=575-5x | | 3x^5=15x^4 | | 4=575-5x | | 4=575-5 | | a=v+y-z | | x=v-a+8 | | 2=575-5x | | x/3-3=-4 | | c-v+x=b | | -1.1-5x=7.4 | | (6x+14)+(9x+5)= | | x-2.2=3.4 | | y-v+(-1)=z | | -.4(.5x-8)=12 | | 5/7(x-2)-40/7=-6 | | x-(6-v)=z | | 5(v-1)-v=4(v-1)+9 | | -.04(.5x-8)=12 | | x^3+8x^2+5x-30=0 | | b=c-v+x | | 3x+7+5x=39 | | y^2-3y-x+4=0 | | 8(x+2)=7(x-3)+x | | 16b+-5=3(4b+9) |